Relative Occurrence of First Episode Wheezing in Children Who Post COVID-19 with Pneumonia and Without Pneumonia - Kettim, Nutnicha; Promnam, Patcharapond; Thanetrapha, Samitanan (Health Science Clinical Research, 2023)
ABSTRACT Objective: To study relative occurrence of 1st episode wheezing in children with history of being diagnosed as having COVID-19 Pneumonia and COVID-19 without Pneumonia Methods: Studying children with history of being diagnosed with COVID-19 0-15 years old who were admitted at inpatient department January 13rd, 2020 – August 4th, 2022. Patients’ data was retrospectively obtained from ICD-10 medical records. Patients were classified into 2 groups as patients with a history of COVID-19 Pneumonia 70 cases group and patients with a history of COVID-19 without Pneumonia 70 cases. 1st episode wheezing was compared relative risk between 2 group. All data were analyzed by descriptive and analytic statistics. Results: Relative occurrence of 1st episode wheezing in child patients with a history of being diagnosed as having COVID-19 with pneumonia had higher risk of 1st episode wheezing than child patients with a history of COVID-19 without pneumonia 22 times statistical significance (95% CI 2.00- 242.15, p=0.011) Conclusions: Occurrence of 1st episode wheezing in child patients with a history of being diagnosed as having COVID-19 with pneumonia and without pneumonia is not different. Keywords: 1st episode wheezing, Long COVID-19, Post COVID-19, COVID-19 Pneumonia